Management of women with low grade cytology: how reassuring is a normal colposcopy examination?. (20th June 2014) - Cruickshank, ME; Cotton, SC; Sharp, L; Smart, L; Walker, LG; Little, J; the TOMBOLA Group
<x xml:space="preserve">Abstract</x> Objectives To determine the rate of cervical intraepithelial neoplasia grade 2 (CIN2+) in women with low grade cervical cytology and a normal colposcopy examination over 3 years of follow‐up. Design Cohort study within a randomised controlled trial. Setting NHS Cervical Screening Programmes in Grampian, Tayside and Nottingham. Population Eight hundred and eighty‐four women aged 20–59 years with borderline nuclear abnormalities (BNA) or mild dyskaryosis with a normal and adequate colposcopy examination. Methods Samples at baseline were tested for 14 high‐risk (Hr) types using GP5+6+ methodology and for HPV 16 and 18 using type‐specific primers. Women were followed up post‐colposcopy by cervical cytology at 6‐month intervals in primary care. After 3 years, women were invited for an exit colposcopy examination and underwent LLETZ if any colposcopic abnormality was identified. Main outcome measures Absolute and relative risks of CIN2+ during follow‐up and/or at exit colposcopy. Results The median age was 36 years. The absolute risk of developing CIN2+ within 3 years was 1.86 per 100 woman years and for CIN3+, 0.64 per 100 woman years. One microinvasive cancer was identified. The relative risk (RR) was highest for women with initial mild dyskaryosis who were HrHPV‐positive (RR 5.86, 95% confidence interval 2.53–13.56) compared with women with BNA who were HrHPV‐negative. Conclusion For women with low grade cervical cytology, the risk of a high grade CIN within 3 years of a normal colposcopy examination is low. Women can be reassured that, even with a positive HPV test, the risk of developing CIN2 or worse is sufficiently low to return to the routine 3‐year recall.